Seroprevalence of SARS-CoV-2 Infection Among People Living with HIV in Libreville, Gabon - Samira Zoa-Assoumou; Hervé M’boyis-Kandem; Pelagie Saphou-Damon; Davy Ulrich Leger Mouangala; Guy-Francis Nzengui; Marina Mbani-Okoumba; Claudine Kombila-Koumavor; Gael Mourembou; Brama Ibrahim; Angelique Ndjoyi-Mbiguino (COVID)
(1) Objectives: The burden of SARS-CoV-2 infection in people living with HIV (PLHIV) in Gabon is unknown. (2) Methods: We conducted a cross-sectional seroprevalence study of SARS-CoV-2 immunoglobulin (Ig) G/M antibodies in PLHIV in Libreville from April 2022 to April 2023 after the fourth wave of the pandemic. We used the WANTAI SARS-CoV-2 Ab ELISA targeting the SARS-CoV-2 spike, receptor-binding domain. (3) Results: Among 480 samples tested, the seroprevalence of IgG antibodies to SARS-CoV-2 spike protein was 87.5% (95% confidence interval (CI) 77.7–97.3%). History of SARS-CoV-2 diagnosis, ART treatment, and TCD4 lymphocyte count were not found to be associated with the presence of antibodies against SARS-CoV-2 among the study participants. However, having a detectable viral load (p = 0.0001), being vaccinated (COVID-19 vaccine, p = 0.04), and a history of COVID-19 (p < 0.0001) symptoms were associated with a higher risk of having anti-SARS-CoV-2 antibodies. (4) Conclusions: By early 2023, PLHIV in Gabon had high rates of SARS-CoV-2 seropositivity. To our knowledge, this is the first study to determine the seroprevalence of SARS-CoV-2 antibodies in PLHIV in Gabon. This study provides further evidence of anti-SARS-CoV-2 seroconversion in the absence of any vaccination in a particular target population. The surveillance of diseases of global health concern in PLHIV is crucial to estimate population-level exposure and inform public health responses.